MicroRNA-Mediated Regulation of ITGB3 and CHL1 Is Implicated in SSRI Action - Oved, Keren; Farberov, Luba; Gilam, Avial; Israel, Ifat; Haguel, Danielle; Gurwitz, David; Shomron, Noam (Frontiers in Molecular Neuroscience, 2017)
Background: Selective serotonin reuptake inhibitor (SSRI) antidepressant drugs are the first-line of treatment for major depressive disorder (MDD) but are effective in <70% of patients. Our earlier genome-wide studies indicated that two genes encoding for cell adhesion proteins, close homolog of L1 (CHL1) and integrin beta-3 (ITGB3), and microRNAs, miR-151a-3p and miR-221/222, are implicated in the variable sensitivity and response of human lymphoblastoid cell lines (LCL) from unrelated individuals to SSRI drugs. Methods: The microRNAs miR-221, miR-222, and miR-151-a-3p, along with their target gene binding sites, were explored in silico using miRBase, TargetScan, microRNAviewer, and the UCSC Genome Browser. Luciferase reporter assays were conducted for demonstrating the direct functional regulation of ITGB3 and CHL1 expression by miR-221/222 and miR-151a-3p, respectively. A human LCL exhibiting low sensitivity to paroxetine was utilized for studying the phenotypic effect of CHL1 regulation by miR-151a-3p on SSRI response. Results: By showing direct regulation of CHL1 and ITGB3 by miR-151a-3p and miR-221/222, respectively, we link these microRNAs and genes with cellular SSRI sensitivity phenotypes. We report that miR-151a-3p increases cell sensitivity to paroxetine via down-regulating CHL1 expression. Conclusions: miR-151a-3p, miR-221/222 and their (here confirmed) respective target-genes, CHL1 and ITGB3, are implicated in SSRI responsiveness, and possibly in the clinical response to antidepressant drugs.